2010
DOI: 10.1021/ma1003776
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Complementary Multiply Hydrogen Bonded End-Functional Polymer Blends

Abstract: Blends of diamidonaphthyridine (Napy) end-functional poly(n-butyl acrylate) (PnBA) and ureidopyrimidinone (UPy) end-functional poly(benzyl methacrylate) (PbnMA) were studied as a function of the component molecular weights to compare with prior theoretical predictions.1 Macroscopic phase separation was observed to be prevented by the reversible association of end-functional polymers to form supramolecular diblock copolymers, resulting in stabilization of the interface between the polymers. At low molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 82 publications
1
69
0
Order By: Relevance
“…[1][2][3][4] Theoretical work has shown that the domain size and morphology of the phase-separated structures critically depend on the strength of the interpolymer noncovalent interactions. [5][6][7][8][9][10] To achieve these attractive enthalpic interpolymer interactions, end-functionalized homopolymers have been prepared with functional groups capable of noncovalent assembly such as hydrogen bonding, [11][12][13][14][15][16][17][18][19][20] ionic, 21 transition-metal, 22,23 host-guest, [24][25][26] and fluorophilic 27 interactions. Typically, these functional groups are attached to a homopolymer via a short, aliphatic spacer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] Theoretical work has shown that the domain size and morphology of the phase-separated structures critically depend on the strength of the interpolymer noncovalent interactions. [5][6][7][8][9][10] To achieve these attractive enthalpic interpolymer interactions, end-functionalized homopolymers have been prepared with functional groups capable of noncovalent assembly such as hydrogen bonding, [11][12][13][14][15][16][17][18][19][20] ionic, 21 transition-metal, 22,23 host-guest, [24][25][26] and fluorophilic 27 interactions. Typically, these functional groups are attached to a homopolymer via a short, aliphatic spacer.…”
Section: Introductionmentioning
confidence: 99%
“…KEYWORDS: atom transfer radical polymerization (ATRP); diffusion-ordered spectroscopy; hydrogen bonding; supramolecular diblock copolymers INTRODUCTION The combination of supramolecular chemistry and the controlled phase separation of diblock copolymers can result in a wealth of nanoscale morphologies with applications ranging from semiconductor integrated circuit design to the development of subnanometer porous films for separation processes. [1][2][3][4] Theoretical work has shown that the domain size and morphology of the phase-separated structures critically depend on the strength of the interpolymer noncovalent interactions.5-10 To achieve these attractive enthalpic interpolymer interactions, end-functionalized homopolymers have been prepared with functional groups capable of noncovalent assembly such as hydrogen bonding, [11][12][13][14][15][16][17][18][19][20] ionic, 21 transition-metal, 22,23 host-guest, 24-26 and fluorophilic 27 interactions. Typically, these functional groups are attached to a homopolymer via a short, aliphatic spacer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By investigating 2,7-diamido-1,8-naphthyridine (DAN) and UPy end-functionalized PnBAs and poly(benzyl methacrylate)s it was found that the phase behavior and microstructure in the bulk were controlled by hydrogen bonding interactions [100] as well as by temperature changes, directly influencing the compatibility of the phases [101]. Thus, UPy dimerization led to compatibilization, whereas complementary hydrogen bonding interactions resulted in significant reduction in macroscopic phase separation [100] and in the formation of supramolecular diblock copolymers [101] or graft polymers [102].…”
Section: Bis(urea)-based Hydrogen Bonding Interactionsmentioning
confidence: 99%
“…Thus, UPy dimerization led to compatibilization, whereas complementary hydrogen bonding interactions resulted in significant reduction in macroscopic phase separation [100] and in the formation of supramolecular diblock copolymers [101] or graft polymers [102]. Supramolecular alternating copolymers were formed by hydrogen bonding interactions between a 1:1 mixture of a bis-UPy-functionalized polyTHF and a bis-DAN-functionalized low molar mass linker [103].…”
Section: Bis(urea)-based Hydrogen Bonding Interactionsmentioning
confidence: 99%